Risk factors for hypothermia in patients under general anesthesia: Is there a drawback of laminar airflow operating rooms? A prospective cohort study. (September 2015) - Yang, Lu; Huang, Chan-Yan; Zhou, Zhi-Bin; Wen, Zhi-Shuang; Zhang, Guan-Rong; Liu, Ke-Xuan; Huang, Wen-Qi
Abstract: Introduction: The aim of this study was to estimate the prevalence and risk factors of hypothermia under general anesthesia in a large domestic hospital. Method: All of the consecutive 1840 patients who underwent scheduled surgery between August and December 2013 were admitted to the study. The nasopharyngeal temperature was measured, and the following variables were also recorded: sex, age, type of surgery, duration of anesthesia, active warming devices and type of operating room. Univariate and multiple regression binary logistic analyses with odds ratios (ORs) and 95% confidence intervals (95% CIs) were used to assess the relationship between each clinical risk factor and hypothermia. Results: The prevalence of hypothermia under general anesthesia was 25.7%. In the univariate analysis, the risk factors of hypothermia were age, the duration of anesthesia, the type of operating room and the type of surgery. Sex was not included. In the multiple logistic regression analysis, the significant risk factors of hypothermia were advanced age, laminar airflow operating rooms and general surgeries. Conclusion: Intraoperative hypothermia is still common and should therefore receive serious attention. Advanced age, the use of a laminar airflow operating room and general surgeries are high risk factors of hypothermia. Highlights: The use of a laminar airflow operating room is one risk factor for hypothermia. Older patients are at risk of operating room hypothermia. Patients scheduled for general surgeries are also at high risk.